Investigation of the dynamic behaviour of an automobile wiper system. (2016) - Qin, Wenjie; Yu, Zhe; Hou, Qingdong
A rigid-flexible multi-body system dynamic model of a passenger vehicle windscreen wiper system is established in this study to investigate the systems dynamic behaviour. To simulate the impact forces applied by the blades on the windshield and the pressure force distributions along the wiper blades, the blades are modelled as flexible bodies in consideration of their bend and twist deformations. On the basis of the dynamic analysis results, structure improvement measures, including changing the torsional stiffness of the neck of the blade segment and modifying the positions of the pivot points on the blades, are implemented to reduce the reversal impact and improve the wiping uniformity.